The very best of Tad Williams. - Williams, Tad (Tachyon Publications, 2014)
"The Very Best of Tad Williams collects Williams' finest work in multiple genres, including epic fantasy, urban fantasy, and YA. These superlative tales, many of which were previously available only in limited editions, introduce dragons, wizards, assassins, heroes, and fools--even a few cyberpunks."--Amazon website.